The Effect of Diary to Teach Writing for Tenth Grade Students of SMKN 1 Madiun in the Academic Year of 2022/2023 - Charisma Erviana; Vita Vendityaningtyas (SELL (Scope of English Language Teaching, Linguistics, and Literature) Journal, 2023)
Diary is a book about personal notes, activities that will be carried out every day or unforgettable experiences in the form of stories of hearts and minds. Diary is one of the media that can be used in learning to write, especially writing experience texts. This research aims to determine the effect of diaries on writing for vocational high school students. The quasi-experimental research used in this study. The participants were the students of SMKN 1 Madiun. The researcher used a writing test with pre-test and post-test to collect the data. The result of the data analysis shows that there is a significant difference in students’ recount text writing skills between the experimental class and the control class. Students who are taught using a diary gain higher scores than students who are taught using conventional teaching. The mean score of the experimental class is 85,11 while the mean score of the control class is 67,02. It can be stated that the use of diary media can improve students’ ability in developing the idea. The use diary makes the students critical and active in the process of learning to write. So, it can be concluded that the media diary is the best way to teach writing recount text.